2005
DOI: 10.1007/s00330-005-2697-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intracoronary attenuation on coronary plaque measurements using multislice computed tomography: observations in an ex vivo model of coronary computed tomography angiography

Abstract: Influence of intracoronary attenuation on coronary plaque measurements using multislice computed tomography: observations in an ex vivo model of coronary computed tomography angiography Abstract Assessment of attenuation (measured in Hounsfield units, HU) of human coronary plaques was performed using multislice computed tomography (MSCT) in an ex vivo model. In three ex vivo specimens of left coronary arteries in oil, MSCT was performed after intracoronary injection of four solutions of contrast material (400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
111
3
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(124 citation statements)
references
References 20 publications
5
111
3
5
Order By: Relevance
“…However, there are wide distributions of CT densities among studies, which may be attributed mainly to differences in contrast flow rate between studies. Schroeder et al 11 and Cademartiri et al 12 demonstrated that an ex vivo model that contrasts flow rate and contrast concentration within the coronary artery may affect density measurement. In addition, small microcalcification within the plaque, which was frequently found around the necrotic core and not grossly visualized on multidetector computed tomogram, may have affected density measurement through partial volume and beam-hardening effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are wide distributions of CT densities among studies, which may be attributed mainly to differences in contrast flow rate between studies. Schroeder et al 11 and Cademartiri et al 12 demonstrated that an ex vivo model that contrasts flow rate and contrast concentration within the coronary artery may affect density measurement. In addition, small microcalcification within the plaque, which was frequently found around the necrotic core and not grossly visualized on multidetector computed tomogram, may have affected density measurement through partial volume and beam-hardening effects.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, it is considered that the large variability of these measurements makes for an accurate classification of non-calcified 'plaque types' difficult. 19, 20 Recently, 1 criterium for soft plaque was reported to be a CT density value <30 HU. 17 Accordingly, our results indicating that the portions without a HDA in attenuated plaque included areas <30 HU, might support the hypothesis that lipid-laden atheroma is one of the components of attenuated plaque.…”
Section: Discussionmentioning
confidence: 99%
“…As the concept is based on the CT value, the plaque CT value is influenced by contrast media density in the vessel lumen, 13 calcium blooming effects and motion artifacts. In the present case, the evaluation of plaque with CCP was considered to be correct, because both lumen CT values (approximately 300 HU) at the reference sites of the first and second CCP examination were similar and only slightly affected by those of the plaques (Figures 1,3).…”
Section: Discussionmentioning
confidence: 99%